PENGARUH TEKANAN KETAATAN, KOMPLEKSITAS TUGAS, DAN PENGALAMAN AUDITOR TERHADAP PERTIMBANGAN AUDIT - YULIA SYAFITRI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2016)
The research theme is the financial and banking institutions. This study aims to analyze empirically about the effect of obedience pressure, complexity of task, and audit consideration of audit experience. Obedience pressure can arise from 3 different sources: private disturbance, external disturbance, and or disturbance from organization. Obedience pressure from the superior and audit experience can affect the type of mature judgment taken by an auditor. This study used a sample of 53 independent government auditors who worked at the Representative Audit Board of the Republic Of Indonesia Of West Sumatera Province. This study uses a questionnaire instrument provided directly to the auditors by the researcher. The results of this study indicate that obedience pressure from the superior and audit experience can affect the audit judgment, while the complexity of task doesn’t affect the audit judgment significantly. The results of this study are expected used by the auditor to improve the professionalism continually in giving the appropriate considerations.